Inguinal Hernia Repair Using Absorbable Biosynthetic Mesh Versus Permanent Polypropylene Mesh: A Preliminary Comparative Study of 1-Year Outcomes - Ferdinand Köckerling; Kasia Bradbury; Catherine C. Steele; Daniela Adolf; Amit Badhwar (Journal of Abdominal Wall Surgery, 2025)
IntroductionInguinal hernia repair with synthetic mesh became a gold standard due to durability and low recurrence rates. With the growing popularity of absorbable meshes in abdominal wall repairs, we evaluated performance of absorbable biosynthetic mesh and permanent synthetic mesh in inguinal hernia repair.MethodsA retrospective analysis of patients undergoing elective unilateral inguinal hernia operations with absorbable biosynthetic (Phasix™ Mesh and Phasix™ ST Mesh) and permanent synthetic (Bard™ Soft Mesh and Ventralight™ ST Mesh) from Herniamed was performed. Patients in both mesh groups were matched using 1:1 propensity score matching. Complications (intraoperative, general, and postoperative) and clinical outcomes at 1-year follow-up were reported and compared between matched pairs.ResultsAmong 1,185,067 patients from 954 centers, 8,286 patients fit the inclusion criteria, 75 patients with absorbable mesh – Phasix group, and 8,211 patients with synthetic mesh – PP group. After propensity score matching, there were 64 matched pairs. There were no statistical differences between groups observed in intraoperative, general, or postoperative complications. At 1-year follow-up, there were no recurrences reported for either group. There were no significant differences in 1-year outcomes including pain (on exertion, at rest, and requiring treatment) between Phasix and PP groups.ConclusionComplications and 1-year outcomes following inguinal hernia repair are not statistically different between absorbable biosynthetic and permanent synthetic mesh. Despite the absorbable nature of the biosynthetic mesh, the 1-year outcomes are similar to permanent synthetic mesh. However, the study was conducted on a small cohort and future studies with longer follow-up are needed to evaluate advantages, if any, over the other mesh types.